2006
DOI: 10.1093/ajcn/84.3.580
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A supplementation in children with poor vitamin A and iron status increases erythropoietin and hemoglobin concentrations without changing total body iron

Abstract: In children deficient in vitamin A and iron, vitamin A supplementation mobilizes iron from existing stores to support increased erythropoiesis, an effect likely mediated by increases in circulating EPO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
2
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(137 citation statements)
references
References 56 publications
8
117
2
10
Order By: Relevance
“…Nutritional surveys have shown a close association between vitamin A deficiency and anemia (Mejia and Chew, 1988;Bloem et al, 1989). Vitamin A repletion may reduce anemia by improving utilization of stored Fe for erythropoiesis (Zimmermann et al, 2006), and by enhancing immunity and reducing the anemia of infection (Semba and Bloem, 2002). Intervention studies in preschool and school-going children also confirm that vitamin A supplementation improves Hb concentration and other measures of Fe status (Mohanram et al, 1977;Mejia and Chew, 1988;Mwanri et al, 2000).…”
Section: Urban Andmentioning
confidence: 99%
“…Nutritional surveys have shown a close association between vitamin A deficiency and anemia (Mejia and Chew, 1988;Bloem et al, 1989). Vitamin A repletion may reduce anemia by improving utilization of stored Fe for erythropoiesis (Zimmermann et al, 2006), and by enhancing immunity and reducing the anemia of infection (Semba and Bloem, 2002). Intervention studies in preschool and school-going children also confirm that vitamin A supplementation improves Hb concentration and other measures of Fe status (Mohanram et al, 1977;Mejia and Chew, 1988;Mwanri et al, 2000).…”
Section: Urban Andmentioning
confidence: 99%
“…Vitamin A repletion in vitamin A-deficient rats enhanced optimum erythropoiesis and iron mobilization from iron stores (Roodenburg et al, 1996). A number of studies among children, aged 1-13 years, showed significant improvement in mean haemoglobin (Hb) concentrations and a decrease in anaemia prevalence after supplementation with vitamin A capsules (Bloem et al, 1989(Bloem et al, , 1990Smith et al, 1999;Zimmermann et al, 2006). Greater improvements in iron status were also seen among anaemic 1-to 8-year-old (Mejia and Chew, 1988) and 9-to 12-year-old children (Mwanri et al, 2000) and in pregnant women (Panth et al, 1990;Suharno et al, 1993;Kolsteren et al, 1999;Muslimatum et al, 2001) when iron and vitamin A supplements were given simultaneously rather than when iron or vitamin A were supplemented alone.…”
Section: Introductionmentioning
confidence: 99%
“…Although its role in vision is well known, VA also participates in the regulation of cell proliferation and differentiation, reproduction, fetal development, immune function and many other metabolic processes (McLaren and Frigg, 2001;Zimmermann et al, 2006). Vitamin A deficiency (VAD) is a public health problem among preschool children in 118 countries of the world.…”
Section: Introductionmentioning
confidence: 99%